The Impact of Cyberattacks on Efficient Operations of CAVs - McManus, Ian; Heaslip, Kevin (Frontiers in Future Transportation, 2022)
The implementation of connected and automated vehicles promises increased safety and efficiency by leveraging advances in technology. With this new technology, some vulnerabilities could lead to cyberattacks. Without a focus on cybersecurity, vehicles may be attacked, reducing the efficiency and safety advantages promised through technological advancement. This research performed an impact analysis on traffic operations of cyberattacks on Vehicular Ad-Hoc Networks (VANET). A roadway traffic and communications simulation was created using the Veins modeling platform that incorporated V2X communication and could model Denial of Service (DoS) and Man in the Middle (MITM) attacks on an urban street network. The number of compromised intersections and attack success rate were varied to understand the impact of each attack scenario. Each attack’s worst-case scenario resulted in an over 20% increase in travel time delay per vehicle as the attack severity increased. Also, the attacks had a wide variation in delay upon the transportation network, decreasing the travel time reliability and the ability for road users to predict delay on their journey.